Análise da aplicação dos modelos C.H.A. e T-SHAPED para avaliação de competências em profissionais de TI - Silva, Antonio Carlos da (2017)
Investigating the skills of professionals working in Information Technology, whether in technical functions or in business management, is currently a strategic factor for organizations. Many companies operating in Brazil use a competency model called C.H.A., which assists in the evaluation of people from any business area without the due deepening of specific skills in technology. This research aims to develop an analysis of the adherence of the combination of C.H.A. and the T-SHAPED model, managerial tools for assessing skills in professionals in the technical and IT management area. To obtain the relation between the models the comparative method was used, validating that the two models are similar in the form of evaluating the competence of a market professional. The T-SHAPED model is described as an amplitude of tacit knowledge, formed by domain, theoretical depth and experience that is integrally linked to the knowledge of the C.H.A model. The research methodology is an explanatory type, with a qualitative approach, using interviews with the Delphi method supported by IT and HR managers, and it will be possible to evaluate if the characteristics of these combined models are applicable in the evaluation of the competencies of professionals Information Technology. The results obtained with the specialists pointed out the consensus that the application of these combined models is adherent and that can be applied as a management tool in the support to the management of technology employees of the companies of the national market with respect to their competences.